2019
DOI: 10.1177/1091581819883820
|View full text |Cite
|
Sign up to set email alerts
|

Safety Assessment of Glycerin as Used in Cosmetics

Abstract: This is a safety assessment of glycerin as used in cosmetics. Glycerin functions as a denaturant, fragrance ingredient, hair conditioning agent, humectant, oral care agent, oral health-care drug, skin protectant, skin conditioning agent—humectant, and viscosity-decreasing agent. The Cosmetic Ingredient Review Expert Panel (Panel) reviewed relevant animal and human data. The Panel concluded that glycerin is safe as a cosmetic ingredient in the practices of use and concentration described in this safety assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 30 publications
0
28
0
2
Order By: Relevance
“…In particular, both glycerol and propylene glycol are among the most widely used raw materials in food, cosmetic and pharmaceutical industries. Glycerol shows excellent solubility in water, and, due to its GRAS status, it is very safe to use [29]. Propylene glycol is a colorless, odorless and completely water-soluble solvent very similar to glycerol, also having the GRAS status and high safety [30].…”
Section: Development and Optimisation Of Nanovesicles Loaded With Ooeo And Steomentioning
confidence: 99%
“…In particular, both glycerol and propylene glycol are among the most widely used raw materials in food, cosmetic and pharmaceutical industries. Glycerol shows excellent solubility in water, and, due to its GRAS status, it is very safe to use [29]. Propylene glycol is a colorless, odorless and completely water-soluble solvent very similar to glycerol, also having the GRAS status and high safety [30].…”
Section: Development and Optimisation Of Nanovesicles Loaded With Ooeo And Steomentioning
confidence: 99%
“…For the 50% glycerol with topical application, 50% glycerol is safe for in vivo human skin applications and been allowed as human skincare products. The safety assessment of The Cosmetic Ingredient Review Expert Panel (CIR) reported that glycerin can be used at concentrations up to 78.5% in leave-on products 53 . The results of 50% glycerol topical application will help future in vivo human skin trials.…”
Section: Investigating the Optical Clearing Effects Of 50% Glycerol Imentioning
confidence: 99%
“…Natrium Klorida adalah untuk meningkatkan viskositas SLES , juga penambahan glyceryl stearat mempercantik penampilan sabun menjadi putih dengan hasil busa lebih creamy (Elder, 1982). Cocomide DEA sebagai pembentuk busa seperti halnya SLES (Prayadnya et al, 2017) akan memberikan sensasi bahwa sabun cair ini memiliki daya bersih, sedangkan gliserin memberikan rasa lembut pada kulit (Becker et al, 2019).…”
Section: Introductionunclassified